Student as teacher – alternative revision method via Quizizz app - Amirul Mukminin Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Revision is one of the most important parts of learning activities, especially to test students' level of understanding. However, the 21st century learning situation saw the process of revision in classroom that is still fully mastered by teachers. This research aims to look at the effectiveness of the game-based application Quizizz as a revision medium as well as to develop students' self-learning. Through the use of Quizizz, students need to prepare a quiz-based questions for a spesific topic, and the fellow students will answer the questions. QuasiExperimental research involved 30 undergraduate students of social science course where the data was obtained through pre-test and post-test scores as well as questionnaires. The data were analyzed using the T-Test Independent Test for comparison of scores and Simple Linear Regression test for the regression analysis between variables. Comparative analysis of scores between pre and post-intervention test revealed significant differences, with p = 0.000 values recorded. Regression analysis showed a significant association between the intervention method and the increase of students’ course content mastery and self-learning skill. The results show that the respondents build their knowledge of the content on their own through the use of Quizizz as a tool, compared to the achievements shown through conventional method.